Children born abroad and diagnosed with HIV infection in the UK/Ireland, 2000–08. (29th September 2015) - Masters, J; Peckham, C; Tookey, P
Abstract : Background and Aim: 1117 HIV-infected children were newly diagnosed in the UK/Ireland in 2000–2008, 63% of whom were born abroad. In this analysis the authors explore timing of diagnosis, reason for testing and clinical status among those children born outside the UK/Ireland. Methods: Surveillance of paediatric HIV infection in the UK/Ireland is carried out through the National Study of HIV in Pregnancy and Childhood. Children with diagnosed HIV infection are notified through the British Paediatric Surveillance Unit. Data collected include child's date and country of birth, date of arrival in the UK/Ireland, date of HIV and/or AIDS diagnosis, reason for testing and clinical status. Results: Seven hundred and six children were reported who were born abroad: 92% came from sub-Saharan Africa, 91% were infected through mother-to-child transmission (MTCT) (4% via other routes, source of infection not established for 5%) and 51% were male. Most were tested either because a family member was diagnosed with HIV (rising from 39% in 2000 to 62% in 2008 p=0.07) or because the child presented with symptoms (declined from 58% in 2000 to 33% in 2008 p=0.09). Almost half (48%) were diagnosed aged 5–9 years (29% 10–14 years, 17% 1–4 years, <5% aged <1 year or >14 years). Date of arrival in the UK/Ireland was available for 72%: among these, 68% were diagnosed within 12 months of arrival, but 15% had been in the country for at least 2 years before they were diagnosed, and another 5% had arrived more than 5 years previously. A quarter of children have had at least one AIDS indicator disease reported (33% of those diagnosed at <5 years, 22% aged 5–15 years); no symptoms have been reported for 37%. Conclusion: Nearly two-thirds of recently diagnosed children were born abroad and the majority acquired their HIV infection through MTCT in Africa. Although a substantial minority of children presented with symptoms, including AIDS, this has declined in recent years, and there has been a non-significant trend towards these children being tested following the diagnosis of a family member, most likely due to increasing uptake of antenatal screening.